Susceptibility to Entamoeba histolytica intestinal infection is related to reduction in natural killer T-lymphocytes in C57BL/6 mice - Fabrício M.S. Oliveira; Bernardo C. Horta; Luana O. Prata; Andrezza F. Santiago; Andréa C. Alves; Ana M.C. Faria; Maria A. Gomes; Marcelo V. Caliari (Infectious Disease Reports, 2012)
Entamoeba histolytica is a protozoan that causes amoebiasis. Recent studies demonstrated that natural killer T lymphocytes (NKT) are critical for preventing the development of amoebic liver abscess. In spite of that, there are only a handful of studies in the area. Herein, we explored the role of NKT cells in E. histolytica infection using C57BL/6 wild-type and CD1-/- mice. Animals were inoculated with E. histolytica and sacrificed 48 hours later to collect caecum samples that were used for quantitative analyses of lesions, trophozoites, NK1.1+ T lymphocytes and expression of the mucus protein MUC-2 by immunohistochemistry technique. Quantitative analyses confirmed that the frequency of NK1.1+ T cells was significantly lower in samples from C57BL/6 CD1-/- mice as compared to their wild type (WT) counterparts. The extension of necrotic mucosa was larger and the number of trophozoites higher in Entamoeba (Eh)-infected CD1-/- mice when compared with Eh-infected WT mice. In mice from both groups, noninfected (CTRL) and Eh-infected CD1-/-, there was a reduction in the thickness of the caecal mucosa and in the MUC-2-stained area in comparison with CTRL- and Eh-WT mice. Our results showed that NKT lymphocytes contribute to resistance against Entamoeba histolytica infection and to the control of inflammation in the colitis induced by infection. The presence of a normal epithelial layer containing appropriate levels of mucus had also a protective role against infection.